Genome-wide identification, evolution and expression pattern analysis of the GATA gene family in Sorghum bicolor - Yao, Xin; Lai, Dili; Zhou, Meiliang; Ruan, Jingjun; Ma, Chao; Wu, Weijiao; Weng, Wenfeng; Fan, Yu; Cheng, Jianping (Frontiers in Plant Science, 2023)
The GATA family of transcription factors is zinc finger DNA binding proteins involved in a variety of biological processes, including plant growth and development and response to biotic/abiotic stresses, and thus play an essential role in plant response to environmental changes. However, the GATA gene family of Sorghum (SbGATA) has not been systematically analyzed and reported yet. Herein, we used a variety of bioinformatics methods and quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) to explore the evolution and function of the 33 SbGATA genes identified. These SbGATA genes, distributed on 10 chromosomes, are classified into four subfamilies (I-IV) containing one pair of tandem duplications and nine pairs of segment duplications, which are more closely related to the monocot Brachypodium distachyon and Oryza sativa GATA genes. The physicochemical properties of the SbGATAs are significantly different among the subfamilies, while the gene structure and conserved protein motifs are highly conserved in the subfamilies. In addition, the transcription of SbGATAs is tissue-specific during Sorghum growth and development, which allows for functional diversity in response to stress and hormones. Collectively, our study lays a theoretical foundation for an in-depth analysis of the functions, mechanisms and evolutionary relationships of SbGATA during plant growth and development.